Penilaian Tingkat Kesehatan Koperasi Simpan Pinjam Kopwan di Kabupaten Nganjuk - Dwi Kartikasari; Dwi Puji Rahayu (JURNAL AKUNTANSI DAN MANAJEMEN MUTIARA MADANI, 2018)
The purpose of this study was to determine the health level of Kopwan savings and loan cooperatives in Nganjuk Regency in terms of capital aspects, quality of earning assets, and liquidity. This type of research is qualitative descriptive research. The population of this study were all KSPs in the Nganjuk Regency area. The samples studied were 10 KSPs spread across several sub-districts in the Nganjuk Regency. The data used were the accountability reports of the KSP supervisors and supervisors. Data analysis was performed to calculate the health aspects of capital aspects, productive asset quality, and liquidity according to the guidelines of the Deputy Regulation of the Ministry of Cooperatives and SMEs Supervision Number 06 of 2016. The results of this study indicate that the level of soundness of the capital aspect, all KSPs (100%) have sound capital. all Kopwan, namely as many as 9 KSPs (90%) have unhealthy productive asset quality. The health level of the liquidity aspect, almost all KSPs, namely 8 KSPs (80%) have unhealthy liquidity. It is recommended that KSP always pay attention to cooperative health in the fields of finance, especially in aspects of prod asset quality uctive and liquidity